Elementary School Teachers’ Acceptance Factors of Web-Based Learning Media on Energy Material (Current Research in Education: Conference Series Journal, 2024)
The utilization of technology in education has a positive impact on students' behavior and thinking, making them more critical, creative, innovative, and collaborative. Currently, there is a need for the integration of technology into education, including the use of web-based learning media. However, the intention and behavior of teachers, in particular, are key factors in the adoption of web-based learning media. The aim of this research is to investigate the predictive factors of primary school teacher acceptance of web-based learning media for energy-related topics. The research method employed a correlational survey involving variables from the UTAUT 2 model. The results indicate that SI, FC, and PLO have a significant influence on BI and are factors affecting the acceptance of web-based learning media by primary school teachers.